Analysis of Factors Affecting Thinking Critical Student Mathematics in The Online Learning Process for Time Covid-19 Pandemic - Alifya, Age (EduMatika: Jurnal MIPA, 2022)
The COVID-19 pandemic which has spread throughout the world in early 2020 has had an impact on teaching and learning activities in schools. The Ministry of Education and Culture and several regional officials issued policies in the form of changing teaching and learning activities to be carried out online. This study aims to determine how many factors influence students' critical thinking in mathematics in the online learning process during the covid-19 pandemic and to determine the significant factors in influencing students' critical thinking. The population in this study were senior high school students at Tabib Tabanan Jl. Bunga Kardiol Ladang Bambu and the number of samples was 29 students. The instrument in this research is in the form of a questionnaire or questionnaire. The results of this study found that the analysis of students' critical thinking in mathematics in the online learning process during the covid-19 pandemic had a positive effect. In the reliability test, physical condition has a value of 0.679%, meaning that the indicator of physical condition affects critical thinking by 67.9% and anxiety has a value of 0.675%, meaning that the indicator of anxiety affects critical thinking. So it can be concluded that the factor that influences students' critical thinking in learning mathematics is the factor that has the highest score is the physical condition factor. So it is necessary for students to continue to maintain their physical condition in learning so that the results of learning mathematics are optimal